Bullying at Work: Research in Estonia using the Negative Acts Questionnaire Revised (NAQ-R) - Merle TAMBUR; Maaja VADI (Revista de Management Comparat International)
This research presents the preparatory stage for the first study of bullying in Estonia. The aim of the research is twofold: to find out how bullying manifests itself in Estonia, and to develop a research method using the Negative Acts Questionnaire Revised (NAQ-R) in Estonia. The results indicate that bullying poses a serious problem for the respondents. We found that at least one negative act given in the questionnaire has been reported to have occurred "daily" by 16.4% of respondents and "weekly" by 28.3% of respondents. The results reveal that the negative acts presented using the NAQ-R method are understandable for the respondents, and therefore, suitable for use in Estonia. Nevertheless, to carry out the basic research, it is necessary to adjust the definition of bullying to make it easier to understand in the local cultural space.